The Scarlett Brand Social Media Marketing Communications on Purchasing Decisions - Hermawan, Irwan; Tinambunan, Dorothy Christi Lois (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Marketing communications is a form of communication that has the aim of strengthening marketing strategies and applying marketing communications to a company. Apart from that, marketing communications can also be used to introduce, establish and create interactions between companies or partners and consumers who are not part of the company, such as suppliers and consumers. The theories used in this research are communication processes, strategies, SOSTAC model marketing communication strategies by combining IMC, forms of marketing or promotional communications. The research method used is a case study research method with a qualitative approach. This research seeks to find empirical evidence from the research object, how to reveal marketing communication strategies in marketing activities for skin care products on the Scarlet brand and build meaning in the implementation of marketing communication activities. The research results show a correspondence between conceptual patterns predicted based on relevant theories and patterns of empirical findings from case studies. Based on the analysis carried out, the conclusion is that the marketing communication strategy for the Scarlett brand uses a promotional mix in the form of advertising, sales promotion, personal selling and event marketing. Many marketing communication activities are supported by brand holding companies or principals.